Association of achondroplasia with Down syndrome: Difficulty in prenatal diagnosis by sonographic and 3‐D helical computed tomographic analyses. (May 2015) - Kaga, Akimune; Murotsuki, Jun; Kamimura, Miki; Kimura, Masato; Saito‐Hakoda, Akiko; Kanno, Junko; Hoshi, Kazuhiko; Kure, Shigeo; Fujiwara, Ikuma
Abstract Achondroplasia and Down syndrome are relatively common conditions individually. But co‐occurrence of both conditions in the same patient is rare and there have been no reports of fetal analysis of this condition by prenatal sonographic and three‐dimensional (3‐D) helical computed tomography (CT). Prenatal sonographic findings seen in persons with Down syndrome, such as a thickened nuchal fold, cardiac defects, and echogenic bowel were not found in the patient. A prenatal 3‐D helical CT revealed a large head with frontal bossing, metaphyseal flaring of the long bones, and small iliac wings, which suggested achondroplasia. In a case with combination of achondroplasia and Down syndrome, it may be difficult to diagnose the co‐occurrence prenatally without typical markers of Down syndrome.